Acrylate nanolatex via self‐initiated photopolymerization. Issue 13 (11th April 2014) - Jasinski, Florent; Lobry, Emeline; Lefevre, Lénaïg; Chemtob, Abraham; Croutxe‐Barghorn, Céline; Allonas, Xavier; Criqui, Adrien
ABSTRACT The use of UV light to initiate emulsion polymerization processes is generally overlooked, whilst extensive literature exists on photocuring of monomer films. In this study, the unique potential of UV light to produce at ambient temperature polyacrylate latexes without initiator was exploited. Although radical initiators are utilized at low concentration, their cost, toxicity, and odor provide incentives for finding alternatives. Starting with concentrated (30 wt %) and low scattering acrylate miniemulsions (droplet diameter <100 nm), it was demonstrated that acrylate self‐initiation can promote an efficient and fast photopolymerization in micrometer‐scale reactor (spectrophotometric cell) and lab‐scale photoreactor. Herein, all kinetic, colloidal, and mechanistic aspects involved in the self‐initiation of acrylate miniemulsion were extensively examined to provide a complete picture. In particular, the effects of droplet size, initiating wavelength, optical path, and irradiance on the course of the polymerization were thoroughly discussed. A diradical self‐initiation pathway is the most likely mechanism. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1843–1853